2012
DOI: 10.1161/circulationaha.111.076398
|View full text |Cite
|
Sign up to set email alerts
|

Is the Extracardiac Conduit the Preferred Fontan Approach for Patients With Univentricular Hearts?

Abstract: W ith improvements in technology, operative technique, and critical care medicine, more and more children with congenital heart disease are surviving into adulthood. As they age, these patients are providing physicians with new challenges, and we are realizing the long-term consequences of our previous interventions. This oftentimes has changed the mode of treatment for subsequent children. Response by Khairy and Poirier on p 2515Fontan palliation for single-ventricle patients was first described in 1971. 1 Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In general, the LT pathway is created by suturing a synthetic baffle inside the atrium[2] and the EC conduit is created from a synthetic tubular graft[3, 4]. Previous studies have shown that the different geometric features of the two connection types are associated with different hemodynamic characteristics, but there is no consensus on which is superior[5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…In general, the LT pathway is created by suturing a synthetic baffle inside the atrium[2] and the EC conduit is created from a synthetic tubular graft[3, 4]. Previous studies have shown that the different geometric features of the two connection types are associated with different hemodynamic characteristics, but there is no consensus on which is superior[5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…ECC Fontan has several advantages over LT Fontan, particularly in terms of energy efficiency 1224. The definite difference between LT and ECC Fontan tract is the method of anastomosing the IVC to the PA: baffle in LT and conduit in ECC.…”
Section: Discussionmentioning
confidence: 99%
“…Two large meta-analyses have recently compared surgical strategies and found no differences in early or late mortality and Fontan takedown between ECC and ILT 33 , 149 . Theoretical advantages of both techniques have been discussed extensively in the literature 150 , 151 . Further research should assess contemporary differences in outcomes between modifications and help guide the preferred procedure for future Fontan patients.…”
Section: Remaining Challengesmentioning
confidence: 99%